2010
DOI: 10.1007/s00774-010-0163-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of office-based brief high-impact exercise on bone mineral density in healthy premenopausal women: the Sendai Bone Health Concept Study

Abstract: Although there is ample evidence supporting the effectiveness of physical activity in the prevention and treatment of osteoporosis, there are no previous studies to examine the effect of office-based brief high-impact exercise (HIE) on bone mineral density (BMD) in healthy premenopausal women. This study evaluated the effects of office-based HIE on BMD in healthy premenopausal Japanese women. Ninety-one healthy premenopausal women were randomized to receive stretching exercise (SE) or HIE (stretching, along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 36 publications
1
41
0
3
Order By: Relevance
“…The exercise intervention in three studies [18,19,24] comprised of brief bouts of highimpact jumping exercises 6 days in a week. Similar interventions were carried out by two other studies [21,26] on alternate days (three sessions per week). Bailey and Brooke-Wavell [20] had three intervention groups who completed the same hopping exercise on 2, 4 or 7 days per week.…”
Section: Interventionmentioning
confidence: 92%
See 4 more Smart Citations
“…The exercise intervention in three studies [18,19,24] comprised of brief bouts of highimpact jumping exercises 6 days in a week. Similar interventions were carried out by two other studies [21,26] on alternate days (three sessions per week). Bailey and Brooke-Wavell [20] had three intervention groups who completed the same hopping exercise on 2, 4 or 7 days per week.…”
Section: Interventionmentioning
confidence: 92%
“…Premenopausal status was based on self-completed lifestyle and menstrual history questions. The sample size varied from 42 [21] to 91 participants [26]. Only three studies [20,24,26] reported a power calculation and estimated achievement of at least 80% power to detect between 2% and 3% differences in BMD of premenopausal women in response to the brief high-impact exercise intervention at the 0.05 alpha level.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations